1998
DOI: 10.1161/01.cir.98.19.2010
|View full text |Cite
|
Sign up to set email alerts
|

Admission to Hospitals With On-Site Cardiac Catheterization Facilities

Abstract: Background-Admission to a hospital with a capability for cardiac procedures is associated with a higher likelihood of referral for a cardiac procedure but not with a better short-term clinical outcome. Whether there are differences in long-term mortality and resource consumption is not clear. We sought to determine whether elderly Medicare patients with acute myocardial infarction admitted to hospitals with on-site cardiac catheterization facilities have lower long-term hospital costs and better outcomes than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 24 publications
3
27
0
3
Order By: Relevance
“…[15][16][17] It was previously reported that AMI patients admitted to revascularization-capable sites are more frequently revascularized with modest or no survival advantage. 9,18,19 The SHOCK trial, however, demonstrated that AMI patients with CS who were randomly assigned to emergency revascularization had an absolute risk reduction of 12.8% in 6-month mortality rate. 2 Yet, the impact of admission hospital type on survival remains unknown in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] It was previously reported that AMI patients admitted to revascularization-capable sites are more frequently revascularized with modest or no survival advantage. 9,18,19 The SHOCK trial, however, demonstrated that AMI patients with CS who were randomly assigned to emergency revascularization had an absolute risk reduction of 12.8% in 6-month mortality rate. 2 Yet, the impact of admission hospital type on survival remains unknown in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…8 The study by Krumholz et al 8,9 found no significant difference in hospital costs during the 3 years after the initial admission for patients admitted to hospitals with and without cardiac catheterization capability. Despite similar findings, the study variables differed substantially from those used in this study.…”
Section: Discussionmentioning
confidence: 97%
“…1 This increase in the number of PCI hospitals could have implications for both the quality and cost of care for patients with AMI. Although several recent studies have examined whether increased PCI capability improves access or outcomes, [1][2][3][4][5][6][7][8] little is known about the cost of treatment for patients admitted with AMI at PCI hospitals versus non-PCI hospitals. This group has previously found that hospital costs for patients admitted to facilities with and without catheterization capabilities did not differ substantially.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…32 The Connecticut substudy of the CCP linked transfers between hospitals to study the impact of on-site catheterization. 33 They linked data for 3 years and found little difference in cost and mortality between hospitals with and without on-site catheterization.…”
Section: -43mentioning
confidence: 99%